2010
DOI: 10.1016/j.semcdb.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of hominin ontogenies

Abstract: Since the beginnings of paleoanthropology, immature fossil hominin specimens have marked important but highly contested cornerstones of research. Long deemed as not representative of a fossil species' morphology, immature hominins are now in the center of scientific attention, and an increasing interest in evolutionary developmental questions has made developmental paleoanthropology a vibrant field of research. Here we report on recent advances in this field, which result from a combination of new methods to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 141 publications
(198 reference statements)
5
63
0
2
Order By: Relevance
“…A neotenic hypothesis of human origin, although inspiring, is controversial and unlikely to hold in a narrow-sense 27 . Regardless of the fine details, the shortening of the face in such a large animal, as us humans, is an exception to the allometry between size and facial proportions that generally holds for mammals.…”
Section: Discussionmentioning
confidence: 99%
“…A neotenic hypothesis of human origin, although inspiring, is controversial and unlikely to hold in a narrow-sense 27 . Regardless of the fine details, the shortening of the face in such a large animal, as us humans, is an exception to the allometry between size and facial proportions that generally holds for mammals.…”
Section: Discussionmentioning
confidence: 99%
“…The slow rate of somatic development in humans, in which developmental immaturity is extended post-natally relative to other primates, has been described by Portmann as 'secondary altriciality' (Portmann 1990: 38), a concept that has become the basis of some important thinking in hominin life history theory and developmental palaeoanthropology (Martin 1983;2008;Zollikofer and Ponce de León 2010;Dunsworth et al 2012). It has also been suggested by Portman and other researchers that the associated phenomenon of foetal brain growth rates being extend ex-utero, and the increase in metabolic requirements this necessitates, may have been facilitated in the hominin lineage by an intensification of parental care (Portmann 1990: 57;Smith and Tompkins 1995: 271;Martin 2007: 78).…”
Section: Discussionmentioning
confidence: 99%
“…Notably Smith and Tompkins (1995) argued that in hominoids major life history trajectories evolved in tandem with increases in brain size. A significant body of literature has consequently built on these studies, resulting in an increasingly refined understanding of the life history and ontogeny of fossil hominins (Minugh-Purvis and McNamara 2002; Thompson, Krovitz and Nelson 2003;Hawkes et al 2006;Robson and Wood 2008;Zollikofer and Ponce de León 2010). In terms of craniofacial variation amongst primates, it has been suggested that males and females share juvenile and sub-adult growth trajectories, but diverge significantly during the period of sexual maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Paleoanthropologists have studied and compared brain growth in humans, extant primates and fossil hominins to better understand the interwoven topics of the evolution of cognition, behavior, life history, energy allocation and childbirth [Martin, 1983;Harvey et al, 1987;Trevathan, 1987;Aiello and Wheeler, 1995;Smith and Tompkins, 1995;Martin, 1996;Rosenberg and Trevathan, 1996;Trevathan, 1996;Leonard and Robertson, 1997;Fairbanks, 2000;Langer, 2000;Rosenberg and Trevathan, 2001;Rosenberg and Trevathan, 2002;Leonard et al, 2003;Coqueugniot et al, 2004;Leigh, 2004;Leigh and Blomquist, 2007;Ponce de León et al, 2008;Weaver and Hublin, 2009;Zollikofer and Ponce de León, 2010;Leigh, 2012;Neubauer and Hublin, 2012]. Humans, having the largest brains among primates, show a special pattern of brain growth: although gestation differs only by a few weeks [Kappeler and Pereira, 2003], human newborns have brains that are about two times larger than those of great apes, yet they have achieved a smaller per-centage of their total brain growth prenatally compared to great apes, they maintain their high fetal growth rates for about 2 years, and then keep growing their brain at lower rates for a longer duration than chimpanzees and other apes [Schultz, 1940[Schultz, , 1941Count, 1947;Holt et al, 1975;Jordaan, 1976;Gould, 1977;Passingham, 1982;Martin, 1983;Dienske, 1986;Smith and Tompkins, 1995;…”
Section: The Evo-devo Approach Of Paleoneurologymentioning
confidence: 99%